Patient factors associated with onabotulinum toxin A treatment outcome in women with detrusor overactivity. Issue 2 (12th January 2016) - Owen, Rhiannon K.; Abrams, Keith R.; Mayne, Christopher; Slack, Mark; Tincello, Douglas G.
Abstract : Objective: To evaluate potential predictors of non‐response to treatment with 200U onabotulinum toxin A (onaBoNTA) in women with refractory detrusor overactivity (DO). Subjects and Methods: A secondary analysis of a randomized trial of 200U onaBoNTA versus placebo in women with refractory DO analyzed baseline and 6 week follow‐up data. Univariate and multivariate logistic regression were used to assess demographic factors and baseline clinical parameters on non‐response to treatment defined as 20% or less improvement in urinary urgency and leakage episodes, 10% or less in voiding frequency, not achieving continence, and "no change" or worse on PGI‐I score at 6 weeks. Results: One Hundred and twenty‐two women were included. Twenty‐nine (23.8%), 24 (19.7%), and 19 (15.6%) were non‐responders to treatment for urgency, voiding, and leakage episodes, respectively. Fifty‐nine (48.4%) failed to achieve continence, and 28 (23%) were non‐responders on the PGI‐I scale. Smoking status (OR: 2.89 95%CI 1.08, 7.73, P = 0.034) predicted non‐response in urgency episodes, and higher baseline leakage episodes (OR: 1.17 95%CI 1.04, 1.31, P = 0.007) predicted non‐response in achieving continence. Increasing age (OR 1.04, 95%CI 1.0, 1.09, P = 0.063) and body mass index (BMI) (OR 1.07, 95%CI 1.0, 1.16, P = 0.065) showed marginal associations with non‐response on the PGI‐I scale. Conclusion: onaBoNTA is an effective treatment for refractory DO, but some fail to respond. For identification of women at risk, our data indicate smokers should be advised of a lesser chance of successful treatment. Older women, those with high BMI and with more severe leakage also have a higher risk of failure. Neurourol. Urodynam. 36:426–431, 2017 . © 2016 Wiley Periodicals, Inc.